The Effectiveness of A cognitive Behavioral Counseling Program in Enhancing Self-Management in Reducing the Academic Procrastination of Tenth grade male Students (Journal Of Educational and Psychological Researches, 2023)
This study aims to find out the effectiveness of a cognitive-behavioral counseling program in enhancing self-management in reducing the academic procrastination of tenth-grade male students. The sample consisted of (26) male students divided into an experimental group of (13) students and a control group of (13) students. Two scales of self-management and academic procrastination were used, prepared by the researcher. The counseling program was prepared by the researcher. The results showed the program's effectiveness in enhancing self-management and reducing academic procrastination in the posttest, as it showed the continuation of this enhancement in self-management and the increase in the reduction of procrastination in the follow-up test of the experimental group